Preliminary Research on Air Passenger Volume Variation in Kilimanjaro International Airport Tanzania - Freddy David Chilongola; Hitapriya Suprayitno; Dewanti Maryoso (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Airport Management needs data on Passenger Volume. Passenger Volume varies annually, monthly, weekly, daily, and hourly. A different aspect of Airport Management needs different data on Pasengger Volume Variation. Each airport has its Variation Characteristics. Kilimanjaro International Airport is a unique airport, as it is located close to a Mountain Kilimanjaro. Knowing it’s Passenger Volume Variation is important. Three Variations have been observed, the monthly, the weekly, and the hourly. The monthly variation shows that the high season happens from July to October. Based on three months of data, the weekly variation shows the inconsistency of the variation pattern. The weekly index of variation could not be developed. While the daily variation shows that high daily volume exists from Friday to Sunday.